Brand essentials - why brands are so important in hotel marketing - Bowie, David (Henry Stewart Talks, 2009)
What are the brand essentials?, Products and brands, Origin of leading hotel brands, Corporate hotel branding, Brand concepts, Brand standards, Brand congruence, Brand awareness and image, Types of brand loyalty, Frequent guest programs, Brand architecture